Integrated farming systems leveraging rainwater harvesting for enhanced productivity, profitability, and sustainability in hyper-arid regions of India - BIRBAL; V, SUBBULAKSHMI; K R, SHEETAL; SONI, M L; RATHORE, V S; JAT, N K; KUMAR, RAKESH (The Indian Journal of Agricultural Sciences, 2025)
Rainfed farming in hyper-arid regions faces significant challenges, including low productivity, poor economic returns and inefficient resource utilization due to erratic rainfall and limited diversification. The study was conducted during July 2019 to June 2023 at ICAR-Central Arid Zone Research Institute, Regional Research Station, Bikaner, Rajasthan to evaluate the productivity, profitability, and resource use efficiency of rainwater harvesting based Integrated Farming System (IFS) model with conventional cropping system of moth bean [Vigna acontifolia (Jacq.) Marechal] and cluster bean [Cyamopsis tetragonoloba (L.) Taub] under rainfed condition. Study assessed a 3.0 ha IFS model integrating arable crops, horticulture, fodder, dairy, vermicomposting, and mushroom cultivation, supported by rainwater harvesting. Results showed that compared to conventional sole cluster bean and moth bean cropping systems, IFS exhibited superior productivity with a mean Cluster Bean Equivalent Yield (CEY) of 7608 kg/ha, significantly surpassing the CEY of 274 kg/ha and 191 kg/ha under conventional rainfed cropping. The IFS achieved annual net returns of ₹1,79,899 with a B:C ratio of 2.40, representing 5.6 and 6.2 times higher net returns than sole cluster bean and moth bean, respectively. In terms of income share, dairy contributed 45.8% of net returns, while horticulture and fodder accounted for 17.8% and 16.5%, respectively. The system demonstrated high water use efficiency (2.498 kg/m³) and a reduced water footprint (400 L/kg). With a Sustainable Value Index (SVI) of 0.560, the IFS model proves to be a resilient, sustainable, and economically viable approach for hyper-arid regions.